The importance of iron and copper accumulation in the pathogenesis of non-alcoholic steatohepatitis - Kemal AKIN; Ali Reşit BEYLER; Muhsin KAYA; Esra ERDEN (Turkish Journal of Gastroenterology, 2019)
-